Formatos de varejo de alimentos: um estudo sobre as preferências do consumidor. - Moura, Thais Lacava de (2005)
The intention of this work is to study the consumer behavior in the choice of retail to purchase food. Being more specific, the work has the objective to identify the profile of the consumers who frequent diverses food retails in the main Brazilian capitals. The identification of the consumers has intention to elaborate recommendations that can be used for retail companies in the strategical decisions of market positioning and adaptation of the store to the consumer profile. So, the work has two bases: the bibliographical revision and the empirical analysis. The bibliographical revision approaches the consumer behavior in general and also in specific food purchase, moreover, it approaches the food retail in Brazil and its characteristics. This revision allows to see the general of consumer behavior and which characteristics of the consumer and others variables are associates with the choice of a retail to purchase food. The empirical analysis has the objective to identify the profile of the consumers of four Brazilian regions in the choice of one or more retail to purchase food. In the conclusion, the bibliographical revision and the empirical analysis are joined to find the similarities and differences between which is found in the literature and that really occurs; because, the characteristics of the consumer and the others variables in the bibliographical revision must reflect on some form the profile of the consumer identified in the empirical research. It is standed out that the fact of the field research to enclose four Brazilian regions, the result in some region can be different of the found in literature because of regional specificities (characteristics of the consumer or local variable). Finally, the elaboration of suggestions and recommendations to the retail companies is made from the junction of the two bases, the theoretical revision and the profile of the consumer.